Modelling and parameterization of the soil-plant-atmosphere system : A comparison of potato growth models - Kabat, P.; Marshall, B.; Vos, J. (Biology - Book Archive pre-2000, 1995)
Eight different models ranging in complexity were compared in a potato modelling case study. Data sets for the comparison case study were provided by the Scottish Crop Research Institute and focused primarily on potential yield, water constrained and nitrogen constrained yield.